2017
DOI: 10.1038/mp.2017.155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of video games on plasticity of the hippocampus

Abstract: The hippocampus is critical to healthy cognition, yet results in the current study show that action video game players have reduced grey matter within the hippocampus. A subsequent randomised longitudinal training experiment demonstrated that first-person shooting games reduce grey matter within the hippocampus in participants using non-spatial memory strategies. Conversely, participants who use hippocampus-dependent spatial strategies showed increased grey matter in the hippocampus after training. A control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 53 publications
3
90
0
3
Order By: Relevance
“…Such individual‐level variety has already been shown to impact the outcome of game play. For example, West and collaborators found differential impact of action video game training on the hippocampus depending on the extent to which individuals adopted spatial or nonspatial strategies for navigation …”
Section: Changes In Games and Gamersmentioning
confidence: 99%
See 1 more Smart Citation
“…Such individual‐level variety has already been shown to impact the outcome of game play. For example, West and collaborators found differential impact of action video game training on the hippocampus depending on the extent to which individuals adopted spatial or nonspatial strategies for navigation …”
Section: Changes In Games and Gamersmentioning
confidence: 99%
“…For example, West and collaborators 74 found differential impact of action video game training on the hippocampus depending on the extent to which individuals adopted spatial or nonspatial strategies for navigation. 74 All of the studies mentioned in the above section are part of a young and promising effort to better understand the impact that playing video games has on the brain. However, most of the evidence is correlational in nature and, although hypotheses are being refined, more studies are needed in order to confirm them.…”
Section: Changes In Games and Gamersmentioning
confidence: 99%
“…Before and after the training procedure the training participants underwent the so-called tunnel task to assess navigation preferences 3, 10 . This task was used, since previous reports on video game plasticity showed differences with navigation strategy 5 . Participants saw a sparse visual flow, at the end of the visual flow they had to indicate the direction where the starting position was.…”
Section: Tunnel Taskmentioning
confidence: 99%
“…Within the present study, we set out to demonstrate that the brain plasticity effects observed in HC [3][4][5] , as well as in DLPFC 3 are elicited by the training of spatial processing within a 3D environment and are not present in a 2D game in which spatial processing is limited. To test this hypothesis, we examined brain plasticity changes after two months of daily video gaming training with the 3D platformer Super Mario 64 and compared it to changes elicited after the same amount of game play in a 2D side-scroller version Super Mario Bros.…”
mentioning
confidence: 93%
See 1 more Smart Citation